The impacts of public mammography screening on the relationship between socioeconomic status and cancer stage - Søren T. Klitkou (Elsevier, 2016)
This study aimed to investigate the relationship between socioeconomic inequality and mortality following the introduction of a public mammography screening program in Norway by exploring the role of change in stage distribution as the mechanism for differences before and after the introduction of the screening program. Attained education level was used as a measure of socioeconomic status in this population-based study. All women aged 50-69 years diagnosed with breast cancer from 1999-2008 and with follow-up data until the end of 2009 were included. The primary endpoint was all-cause mortality. The results of a mediation analysis indicated that the introduction of screening led to stage distribution related reductions of −5.6 (95% confidence interval = −6.7 to −4.5), −2.5 (−3.0 to −2.1), and −1.4 (−1.9 to −0.9) fewer deaths per 1000 women for with a primary school education, secondary school education, and university education, respectively. The study showed that stage distribution explained −5 (−5.9 to −4.1) fewer deaths among women with a university education and −2.4 (−2.9 to −2.0) fewer deaths among women with a secondary school education before program implementation when compared to the group with a primary school education. There were significant reductions in mortality due to stage distribution after program implementation with differences relative to women with primary school of −1.8 (−2.2 to −1.4) and −0.7 (−0.9 to −0.5) fewer deaths in favor of women with university education and secondary school, respectively. The results indicate reduced importance of cancer stage as a reason for differences in mortality by socioeconomic status after the introduction of a public mammography program. Keywords: Breast cancer screening, Socioeconomic status, Cancer stage, Education level, Mortality, Public mammography program